Boundary Control of Slender Beams under Deterministic and Stochastic Loads - Do, Khac Duc (The American Society of Mechanical Engineers, 2017)
This paper first derives equations of motion of extensible and shearable slender beams with large motions under both deterministic and stochastic external loads. Boundary feedback controllers are then proposed to achieve almost surely globally practically asymptotic stability. The control design, well-posedness, and stability analysis are based on a Lyapunov-Type theorem developed for a class of stochastic evolution systems (SESs) in Hilbert space.